2013
DOI: 10.1152/jn.00423.2013
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical spectrotemporal processing with age-related hearing loss

Abstract: Trujillo M, Razak KA. Altered cortical spectrotemporal processing with age-related hearing loss. J Neurophysiol 110: 2873-2886. First published September 25, 2013 doi:10.1152/jn.00423.2013.-Presbycusis (age-related hearing loss) is a prevalent disability associated with aging that impairs spectrotemporal processing, but the mechanisms of such changes remain unclear. The goal of this study was to quantify cortical responses to frequency-modulated (FM) sweeps in a mouse model of presbycusis. Previous studies sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Animal research has shown a direct association between decline in auditory neural selectivity and age-related hearing loss (33,49). If GABA levels influence neural distinctiveness, as our results suggest, then pharmacological treatments that target GABA could be a promising avenue for clinical research aimed at mitigating age-related hearing impairments.…”
Section: Auditory Gaba Decline Predicts Dedifferentiationmentioning
confidence: 63%
“…Animal research has shown a direct association between decline in auditory neural selectivity and age-related hearing loss (33,49). If GABA levels influence neural distinctiveness, as our results suggest, then pharmacological treatments that target GABA could be a promising avenue for clinical research aimed at mitigating age-related hearing impairments.…”
Section: Auditory Gaba Decline Predicts Dedifferentiationmentioning
confidence: 63%
“…The PV+ cells may shape inhibitory components of receptive fields and responses to rapid spectrotemporal cues (Atencio and Schreiner, 2008; Wu et al, 2008). Reduced inhibition may underlie spectrotemporal processing and speech recognition deficits with age (Walton et al, 1998; Mendelson and Ricketts, 2001; Razak and Fuzessery, 2009; Parthasarathy and Bartlett, 2011; Suta et al, 2011; Trujillo and Razak, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Processing of rapidly changing spectrotemporal cues, such as those present in speech, depends on interactions between excitatory and inhibitory components of the auditory neuron receptive field (Zhang et al, 2003; Razak and Fuzessery, 2006, 2008, 2009; Sadagopan and Wang, 2010; Trujillo et al, 2013). Reduced inhibition may, therefore, affect temporal and spectrotemporal processing, and cause speech processing deficits with age (Walton et al, 1998; Mendelson and Ricketts, 2001; Parthasarathy and Bartlett, 2011; Suta et al, 2011; Trujillo and Razak, 2013). The cellular correlates of reduced inhibition in the auditory system remain incompletely characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Although a direct link between presbycusis and age-related degradation of SMI-32 immunoreactivity is still yet to be revealed, there are physiological alterations indicating deteriorated function of fast conducting neurons that may potentially involve SMI-32-ir neurons. In rodents, these alteration include deteriorated processing of fast FM sweeps ( Mendelson and Ricketts, 2001 ), slowing down of responses to the FM sweeps or increased variability to the same auditory stimuli ( Trujillo and Razak, 2013 ).…”
Section: Discussionmentioning
confidence: 99%